Bacterial Lantibiotics: Strategies to Improve Therapeutic Potential - Cotter, Paul D.; Hill, Colin; Ross, R. P. (Current Protein and Peptide Science, 2005)
Lantibiotics are ribosomally-synthesised antimicrobial peptides produced by Gram-positive bacteria that are characterised by the presence of lanthionine and/or methyllanthionine residues. Other unusual post-translationally modified amino acids, most frequently dehydroalanine and dehydrobutyrine, can also be present. While it has been frequently suggested that these peptides have the potential to be utilised in a wide range of medical applications, to date no actual therapeutic applications have been convincingly described. More recently, however, they have been the focus of much attention as a consequence of improved biotechnological capabilities, an improved understanding of lantibiotic biosynthesis and mode of action, and their high specific activity against multi-drug resistant bacteria. This review concerns the fundamental analyses that have revealed the importance of individual amino acids in these peptides and has permitted the implementation of rational mutagenesis strategies ('intelligenetics') to alter individual residues with a view to ultimately widening the active pH range, improve stability, and enhance binding to cell wall targets with the ultimate aim of optimising their antimicrobial activity. It is hoped that as a consequence of this improved knowledge the most suitable application of individual lantibiotics will become apparent. It should also prove possible, in the near future, to generate tailor-made lantibiotics and utilise biosynthetic enzymes to incorporate modified amino acids into non-lantibiotic peptides. In the shorter term, the extensive characterisation of lantibiotics will be instrumental in reassuring drug industry regulators of their safety and facilitate the widespread application of these novel antimicrobial agents in medicine.
Keywords: genetic engineering